Pengesahan Pernikahan Fasid Dalam Rangka Perceraian: Studi Analisis atas Putusan Pengadilan Agama Padang No. 379/Pdt.G/2023/PA.Pdg - Afrizal, Afrizal; Salma, Salma; Efrinaldi, Efrinaldi; Elfia, Elfia (Fakultas Syariah (Syari'ah Faculty ), 2025)
This research aims to analyze the Decision of the Padang Religious Court Number 379/Pdt.G/2023/PA.Pdg which rejected a wife's (plaintiff) divorce suit because the plaintiff was deemed unable to prove the existence of a legal marriage between the plaintiff and the defendant which was carried out under the hand (sirri ). The focus of this research is to find out the basis for the court's considerations in making a decision and to find out whether the decision fulfills a sense of justice for the plaintiff. Researchers use qualitative analysis methods using a normative juridical approach. The results of the research show that the court's most basic consideration in deciding this case was that the marriage of the plaintiff and defendant did not meet the harmony and requirements of marriage in Islam. Even though the marriage was carried out by a marriage guardian, the plaintiff's marriage guardian was not a legal guardian, so the court was of the opinion that the request for legalization of the marriage between the plaintiff and the defendant was not proven, so the plaintiff's divorce claim was rejected because there is no divorce without marriage. After conducting research, decision number 379/Pdt.G/2023/PA.Pdg was deemed not to provide justice and a solution to the chaos in the plaintiff and defendant's household, at least felt by the plaintiff as a wife. The plaintiff was unable to get out of a marriage which he considered to be a broken marriage because the marriage conditions were not met, while the plaintiff and the defendant had actually been together like husband and wife for 15 years without being questioned by anyone else and had also been blessed with two children.